Global Warming and Climate Change: A Critique on International Law and Policy - Lisa P Lukose (Journal of Contemporary Urban Affairs, 2017)
Global warming and climate change, a multidisciplinary topic is a matter of international concern. There are some international environmental treaties related to global warming and climate change. The most significant international agreement in this area is - UNFCCC - the United Nations Framework Convention on Climate Change adopted at the Rio Earth Summit in 1992 and ratified by 195 countries. It mainly deals with greenhouse gases emissions mitigation, adaptation and finance starting in the year 2020. The Kyoto Protocol which extends the 1992 UNFCC mandates State Parties to reduce greenhouse gas emissions: its two basic premises are - global warming exists, and human-made CO2 emissions caused global warming. The Kyoto Protocol came into force in 2005 and each COP has served as the ‘meeting of parties’ to Kyoto Protocol such as COP13 (Bali, 2007), COP15 (Copenhagen, 2009), COP16 (Cancun, 2010), COP17 (Durban, 2011), COP18 (Doha, 2012), COP19 (Warsaw, 2013), COP21 and (Paris, 2015). There are other international legal instruments such as the 1979 Geneva Convention on Long-Range Transboundary Air Pollution. Against this backdrop, this paper will critically examine the existing international legal regime (treaties, conventions, agreements, etc.) on global warming and climate change.